Vestiges of British, German and Polish tax depreciation and amortization regulations in IFRS financial statements - Walkowiak, Marcin Piotr (Economics and Business Review, 2014)
The article compares accounting estimates in IFRS financial statements of manufacturing companies. It shows that after adopting IFRS nation-specific assumptions remained. In all analysed countries there was a tendency to use policies that were based on national laws. The borrowing of laws was more visible in Poland and Germany than in the UK. The accounting policies of companies were mostly based on national tax and accounting laws. When making subjective decisions concerning accounting policies companies tended to base their choice on national law regulations.(original abstract)